Smart Energy Monitoring System - Zakaria, Ahmad Hawari; Ishak, Maizul (Progress in Engineering Application and Technology, 2022)
Smart Energy Monitoring System (SEMS) aims to create a device that can monitor home power consumption remotely using mobile gadgets without disturbing the utility's power meter. By leveraging the Internet of Things (IoT), power consumption can be monitored continuously and ubiquitously. SEMS uses Wi-Fi technology to send data from sensors to the cloud. The voltage data and sensors that have been processed by the ESP32 for the calculation of power consumption is in real time. Calibration using multimeter and clamp meter has been carried out to ensure the accuracy of the readings. The system will provide push notification to user mobile application in the event of overcurrent, undervoltage and overvoltage which is very helpful in case of a circuit breaker failure or fuse.